Conceptualising globalisation: fossil energy, global finance and the labour market. (1st July 2007) - ,
Abstract : Modern globalisation can best be described as a process of expansion and acceleration whereby production, labour and the conditions of life in all regions of the world influence each other. These effects result from the massive use of fossil energy. The imminent shortage of fossil energy (''Peak Oil'') and the disastrous climate effect of the emissions of CO2 . are now major sources of public discontent with globalisation. Global finance, however, exerts a considerable pressure on production to increase growth rates and to reduce labour costs. As a result, labour is also subjected to the dynamics of the global economy with consequences for working conditions, wages, job security, skills and benefits. This is one of the reasons why the ''informal economy'' is growing. An exit exists: from a fossil energy regime to the use of renewable energy and from informal and often precarious forms of labour to solidaristic and cooperative ways to organise production.